Educational and vocational goal disruption in adolescent and young adult cancer survivors. Issue 2 (11th September 2017) - Vetsch, Janine; Wakefield, Claire E.; McGill, Brittany C.; Cohn, Richard J.; Ellis, Sarah J.; Stefanic, Natalie; Sawyer, Susan M.; Zebrack, Brad; Sansom‐Daly, Ursula M.
Abstract: Objective: Cancer in adolescents and young adults (AYAs) can interrupt important developmental milestones. Absence from school and time lost from work, together with the physical impacts of treatment on energy and cognition, can disrupt educational and vocational goals. The purpose of this paper is to report on AYA cancer survivors' experiences of reintegration into school and/or work and to describe perceived changes in their educational and vocational goals. Methods: Adolescents and young adults recruited from 7 hospitals in Australia, aged 15 to 26 years and ≤24 months posttreatment, were interviewed using the psychosocial adjustment to illness scale. Responses were analysed to determine the extent of, and explanations for, cancer's effect on school/work. Results: Forty‐two AYA cancer survivors (50% female) participated. Compared with their previous vocational functioning, 12 (28.6%) were scored as experiencing mild impairment, 14 (33.3%) moderate impairment, and 3 (7.1%) marked impairment. Adolescents and young adults described difficulties reintegrating to school/work as a result of cognitive impacts such as concentration problems and physical impacts of their treatment, including fatigue. Despite these reported difficulties, the majority indicated that their vocation goals were of equal or greater importance than before diagnosis (26/42; 62%), and most AYAs did not see their performance as compromised (23/42; 55%). Many survivors described a positive shift in life goals and priorities. The theme of goal conflict emerged where AYAs reported compromised abilities to achieve their goals. Conclusions: The physical and cognitive impacts of treatment can make returning to school/work challenging for AYA cancer survivors. Adolescents and young adults experiencing difficulties may benefit from additional supports to facilitate meaningful engagement with their chosen educational/vocational goals.